An Overview Of Self-Control In Adolescent With Nomophobia (No Mobile Phone Phobia) - Ilmiah, Gt. Ihda Wardatul; Yusuf, Ah.; Tristiana, RR Dian (Universitas Airlangga, 2021)
Introduction: Self control is important to control the use of smartphones to suit their needs. Low self control is one of the factors that cause nomophobia in smartphone users. The purpose of this study was to gain an understanding of the self-control of adolescents with nomophobia.Method: This study used a qualitative design with a phenomenological descriptive method through in-depth interviews. There were 15 participants with nomophobia, selected using purposive sampling technique. Data were analyzed using Colaizzi analysis. Results: This study identified 12 themes. Self-control of adolescents with nomophobia is influenced by the use of smartphones which raises the theme of reasons for using smartphones, conditions that cause smartphone use, the use of smartphones in life, and various features used on smartphones. Low self control causes adolescent to have difficulty controlling the stimulus to always use a smartphone and trigger nomophobia which is described through the theme of the response of nomophobia, the aspect of nomophobia, and the impact of nomophobia. After experiencing nomophobia, adolescents do self-control to control the impact of smartphone use which raises the theme of self-control efforts, parental control, and the aspects of self-control. Adolescent self-control is influenced by sources and barriers that raise the theme of the sources of self- control and the barriers of self-control.Conclusions: Adolescents with nomophobia have low self-control in using smartphones and controlling self-responses when there is no smartphone. Therefore, adolescent self-awareness and the role of parents are needed to increase self-control to prevent nomophobia and the negative impact of excessive smartphone use.